Respuesta :

Choice A is the answer which is the point (1,-1)

=========================================

How I got this answer:

Plug each point into the inequality. If you get a true statement after simplifying, then that point is in the solution set and therefore a solution. Otherwise, it's not a solution.

-------------

checking choice A

plug in (x,y) = (1,-1)

[tex]y - 2x \le -3[/tex]

[tex]-1 - 2(1) \le -3[/tex]

[tex]-3 \le -3[/tex]

This is true because -3 is equal to itself. So this is the answer.

-------------

checking choice B

plug in (x,y) = (2,4)

[tex]y - 2x \le -3[/tex]

[tex]4 - 2(2) \le -3[/tex]

[tex]0 \le -3[/tex]

This is false because 0 is not to the left of -3, nor is 0 equal to -3. We can cross this off the list.

-------------

checking choice C

plug in (x,y) = (-2,3)

[tex]y - 2x \le -3[/tex]

[tex]3 - 2(-2) \le -3[/tex]

[tex]7 \le -3[/tex]

This is false because 7 is not to the left of -3, nor is 7 equal to -3. We can cross this off the list.

-------------

checking choice D

plug in (x,y) = (3,4)

[tex]y - 2x \le -3[/tex]

[tex]4 - 2(3) \le -3[/tex]

[tex]-2 \le -3[/tex]

This is false because -2 is not to the left of -3, nor is -2 equal to -3. We can cross this off the list.


ACCESS MORE